Nonhomogeneous poisson nonlinear transformations on countable infinite set - Hamzah, Nur Zatul Akmar; Ganikhodjaev, Nasir (Institute Mathematical Sciences, Universiti Putra Malaysia, 2016)
In this paper, we construct the family of nonhomogeneous Poisson quadratic stochastic operators defined on the countable sample space of nonnegative integers and investigate their trajectory behavior. Such operators can be reinterpreted in terms of of evolutionary operator of free population. We show that nonhomogeneous Poisson quadratic stochastic operators are regular transformations